CodeMatcher: A tool for large-scale code search based on query semantics matching - LIU, Chao (Institutional Knowledge at Singapore Management University, 2022)
Due to the emergence of large-scale codebases, such as GitHub and Gitee, searching and reusing existing code can help developers substantially improve software development productivity. Over the years, many code search tools have been developed. Early tools leveraged the information retrieval (IR) technique to perform an efficient code search for a frequently changed large-scale codebase. However, the search accuracy was low due to the semantic mismatch between query and code. In the recent years, many tools leveraged Deep Learning (DL) technique to address this issue. But the DL-based tools are slow and the search accuracy is unstable.In this paper, we presented an IR-based tool CodeMatcher, which inherits the advantages of the DL-based tool in query semantics matching. Generally, CodeMatcher builds indexing for a large-scale codebase at first to accelerate the search response time. For a given search query, it addresses irrelevant and noisy words in the query, then retrieves candidate code from the indexed codebase via iterative fuzzy search, and finally reranks the candidates based on two designed measures of semantic matching between query and candidates. We implemented CodeMatcher as a search engine website. To verify the effectiveness of our tool, we evaluated CodeMatcher on 41k+ open-source Java repositories. Experimental results showed that CodeMatcher can achieve an industrial-level response time (0.3s) with a common server with an Intel-i7 CPU. On the search accuracy, CodeMatcher significantly outperforms three state-of-the-art tools (DeepCS, UNIF, and CodeHow) and two online search engines (GitHub search and Google search).